2013
DOI: 10.1007/s10926-013-9490-5
|View full text |Cite
|
Sign up to set email alerts
|

Striking a Balance: Work-Health-Personal Life Conflict in Women and Men with Arthritis and its Association with Work Outcomes

Abstract: Purpose To examine men and women’s perceptions of inter-role balance/imbalance in work, arthritis, and personal roles and its association with demographic, health and employment factors, including job stress, career satisfaction, job disruptions, absenteeism and perceived productivity losses. Methods Participants were employed, aged ≥40 years and diagnosed with osteoarthritis or inflammatory arthritis. They were recruited through community advertising and rheumatology clinics in two Canadian provinces. Respond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 49 publications
(59 reference statements)
4
29
0
1
Order By: Relevance
“…These synthesis findings emphasized that having a chronic condition further complicates the matter, since the worker needs to balance their work and personal lives while continuously managing their chronic condition and symptoms. This finding is in accordance with other literature on work-life balance and chronic conditions (Bedell, 2008;Gignac et al, 2014;Kaptein et al, 2013). Grawitch et al, who studied work-life balance in light of selfregulation, control and decision making, showed that active decisions need to be made to allocate resources, such as energy which is usually a scarce resource in workers with a chronic condition (Grawitch, Barber, & Justice, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…These synthesis findings emphasized that having a chronic condition further complicates the matter, since the worker needs to balance their work and personal lives while continuously managing their chronic condition and symptoms. This finding is in accordance with other literature on work-life balance and chronic conditions (Bedell, 2008;Gignac et al, 2014;Kaptein et al, 2013). Grawitch et al, who studied work-life balance in light of selfregulation, control and decision making, showed that active decisions need to be made to allocate resources, such as energy which is usually a scarce resource in workers with a chronic condition (Grawitch, Barber, & Justice, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…Participants reporting greater disease activity and fatigue were more likely to report a job disruption and perceived productivity loss, respectively. Results are similar to studies of middle‐ and older‐aged adults with arthritis, which find that fatigue and disease activity are among the most frequently reported health factors related to workplace difficulties . Additionally, greater job control was associated with a lower likelihood of a productivity loss.…”
Section: Discussionsupporting
confidence: 83%
“…Individuals ages $25 years with OA or IA (e.g., rheumatoid arthritis, psoriatic arthritis, ankylosing spondylitis) and who resided in Ontario or British Columbia, Canada were recruited for a longitudinal study on work/health/personal life conflict and its impact on employment (41). To ensure diversity across occupations and to ensure that individuals receiving fewer health care services were not systematically excluded, the sample was purposive and aimed for similar proportions of respondents with OA and IA.…”
Section: Methodsmentioning
confidence: 99%